2021
DOI: 10.1002/asi.24446
|View full text |Cite
|
Sign up to set email alerts
|

Investigative approaches to researching information technology companies

Abstract: Recent events reveal the potential for information technologies to threaten democratic participation and destabilize knowledge institutions. These are core concerns for researchers working within the area of critical information studies—yet these companies have also demonstrated novel tactics for obscuring their operations, reducing the ability of scholars to speak about how harms are perpetuated or to link them to larger systems. While scholars' methods and ethical conventions have historically privileged the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…The present study also turns the preemptive gaze back onto Palantir and seeks to visualize its technological affordances through patent analysis and extraction of topics. We thus simultaneously follow recent calls for critical data and internet studies (Acker and Donovan 2019;Iliadis and Russo 2016) and empirical investigative research of IT companies (Carter, Acker, and Sholler 2021) to understand surveillance platforms like Palantir, which we view as complementary to but distinct from the platform surveillance of social media companies (Murakami Wood and Monahan 2019;Turow and Couldry 2018). Our article views Palantir as a surveillance platform where the primary focus is surveillance services and preemptive decision analytics for facilitating the tracking of people and things both in and outside the US.…”
Section: Metadata Ontologies and Semantic Technologiesmentioning
confidence: 85%
“…The present study also turns the preemptive gaze back onto Palantir and seeks to visualize its technological affordances through patent analysis and extraction of topics. We thus simultaneously follow recent calls for critical data and internet studies (Acker and Donovan 2019;Iliadis and Russo 2016) and empirical investigative research of IT companies (Carter, Acker, and Sholler 2021) to understand surveillance platforms like Palantir, which we view as complementary to but distinct from the platform surveillance of social media companies (Murakami Wood and Monahan 2019;Turow and Couldry 2018). Our article views Palantir as a surveillance platform where the primary focus is surveillance services and preemptive decision analytics for facilitating the tracking of people and things both in and outside the US.…”
Section: Metadata Ontologies and Semantic Technologiesmentioning
confidence: 85%
“…Finally, I have collected and demonstrated the value of different empirical materials, which are also openly available for others to reuse [▸Data availability]. Despite the many known issues and challenges of empirical and historical digital platform research (e.g., Carter et al, 2021;Venturini and Rogers, 2019), I have shown that there are also many opportunities for critical investigations, so long as we know where to look for relevant materials Helmond and van der Vlist, 2021;[▸Ch. 1]).…”
Section: Methodological Implicationsmentioning
confidence: 99%
“…This early research surfaced the very material of many different software objects, which had long been left invisible, and which are so crucial to the study of how platforms govern. Critical approaches to this day often seek to render visible the hidden operations and behaviours of digital platforms and technologies generally, despite the challenges and hurdles they may have raised (e.g., Bounegru and Gray, 2021;Carter et al, 2021;Gray et al, 2018;Rieder and Hofmann, 2020). The case studies presented in subsequent chapters similarly adopt material approaches that contribute to these critical efforts.…”
Section: Digital Platforms Are Powerful Governing Systemsmentioning
confidence: 99%
See 2 more Smart Citations